Studies on Schismatoglottideae (Araceae) of Borneo X. Pichinia, a New Genus from Sarawak, Malaysian Borneo - Wong, Sin Yeng; Boyce, P.C (Singapore Botanic Garden, 2010)
Pichinia S.Y. Wong & P.C. Boyce is described as a new genus from Sarawak, Malaysian Borneo with one species, Pichinia disticha S.Y. Wong & P.C. Boyce. This genus is, so far, known only from the type locality, Pichin, Serian, Bahagian Kuching, Sarawak. The genus is illustated and a key to the Schismatoglottideae is presented.